Producción y comercialización de chocolate orgánico en la provincia de El Oro - cantón Machala. - Cuenca Cumbicos, Jessica Mireya (2018)
In recent years, it has been evident that great changes have taken place in the world economy, which has greatly influenced the international market of food products. Among the changes that stood out during the emergence of organic agriculture to the world market are the process of trade liberalization and the liberation of markets, the consolidation of economic blocs, the strengthening of the institutions that govern international trade, the emergence of new technologies in the field of production, international trade, among others. Cocoa is among the foods in great demand at the international level. Due to its geographical location, Ecuador has adequate climatological conditions for the production of quality cocoa, which have unique tastes and aromas in the world, the cocoa produced in Ecuador has become a high quality raw material for the production of chocolates and foods that are marketed nationally and internationally. The general objective of this project is to: Develop a project to determine the feasibility of developing and marketing organic chocolate, through the offer of a quality product that meets the new demands of consumers in the province of El Oro - Machala canton. The presentation of organic chocolate, its packaging and brand are designed to remain in the minds of consumers, are easy to identify and therefore can be placed in the preference of consumers. The name CHOCOLATERO has been given to the product to star the consumer. Chocolate is a market that is under development, so there is a small but growing number of producers competing to achieve consumer preference, so the company's strategy will focus on satisfying the needs of a company. a different, exclusive and limited segment of customers, those that look for quality products that are at the same time compatible with the conservation of the environment. The strategy with which the price will be determined will be based on competition, quality and differentiation. The sources of income of the venture have their origin in the sale of chocolates, initially they will offer boxes of chocolates containing 4 and 6 bars of chocolate and bar presentation. The project carried out demonstrates the feasibility of the elaboration and commercialization of organic chocolate in the province of El Oro - Cantón Machala. The diagnosis made to the aforementioned project allows obtaining an appreciation of market conditions and potential consumers of organic chocolate, where it is possible to determine commercial allies, consumers and possible marketing channels. Once the company consolidates in the city of Machala, it is possible to carry out an expansion, with the aim of making the product known and that this report a greater profitability, for which it is necessary to carry out product diversification strategies, where the characteristics and consumption habits of people are taken into account.